Sistem Informasi Penyewaan Lapangan Futsal Berbasis Web Dengan Metode Waterfall Menggunakan PHP - Rina Wijayanti; Yety Ariesta Indrastuti; Unsa Hudiana; Dwi Oktafiyah Sumadya; Rena Febrita Sarie; Mei Indrawati (Lembaga Pengembangan Kinerja Dosen, 2025)
Futsal is one of the most popular sports in Indonesia and is widely played by various groups in society, especially students and employees. This popularity is primarily due to the practicality of futsal, which fits well into the limited time available for physical activity. However, the current system used to book futsal courts, particularly at Cendikia Futsal Banyuwangi, still relies on conventional methods such as direct meetings, phone calls, handwritten notes, and informal appointment records. These traditional methods are considered less effective and inefficient because they require more time and are prone to scheduling conflicts, data loss, and miscommunication.The purpose of this research is to develop a solution to overcome the manual court booking and scheduling processes by creating a centralized web-based system. The system is designed and implemented using PHP as the programming language and MySQL as the database management system. This web-based system allows users to access the booking platform online, making it easier and faster for customers to reserve futsal courts.Furthermore, it provides a user-friendly interface for administrators to manage schedules, monitor bookings, and store customer data efficiently. The implementation of this system not only increases efficiency but also reduces the possibility of double bookings and human error. It takes advantage of the rapidly growing Internet infrastructure, enabling users to make reservations at any time and from anywhere. In conclusion, the system significantly improves the operational workflow at Cendikia Futsal and enhances customer satisfaction by offering a modern and accessible reservation method.